- LAGGING BEHIND? THE HUNGARIAN REGULATION OF SUSTAINABLE FINANCE IN SOME ASPECTS: - - Papp, Tekla; Dúl, János (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
In this paper, after a systematic presentation of the theoretical background of the European Union regulation, we examine the Hungarian regulation and legal practice (using the websites of five listed Hungarian companies and the BSE CGR) in connection with the identification of shareholders by the company, the verifiability of the exercise of shareholder’s rights, the remuneration policy and reporting of the public company limited by shares and the approval of legal transactions concluded with related party. We also present certain viewpoints of product governance, with special attention to product approval process and the issue of greenwashing.